2022
DOI: 10.1002/mus.27734
|View full text |Cite
|
Sign up to set email alerts
|

Associations of neuralgic amyotrophy with COVID‐19 vaccination: Disproportionality analysis using the World Health Organization pharmacovigilance database

Abstract: Longitudinal evaluation of SMN levels as biomarker for spinal muscular atrophy: results of a phase IIb double-blind study of salbutamol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
(50 reference statements)
0
5
0
Order By: Relevance
“… 77 In view of the above findings, it can be theorized that mRNA vaccines are more likely to be associated with the subsequent development of PTS, and this hypothesis has been previously been tested and confirmed by Kim et al . 75 This finding is especially important in the context of the COVID-19 pandemic, during which clinicians should have a high index of suspicion of PTS in patients who present with compatible symptoms who have received Comirnaty in the recent past. It is noteworthy that, in the present review, we found that most (78.3%) patients experienced symptoms of PTS ipsilateral to the injection site, which suggests that the pathogenesis may involve the local spread of the inoculum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 77 In view of the above findings, it can be theorized that mRNA vaccines are more likely to be associated with the subsequent development of PTS, and this hypothesis has been previously been tested and confirmed by Kim et al . 75 This finding is especially important in the context of the COVID-19 pandemic, during which clinicians should have a high index of suspicion of PTS in patients who present with compatible symptoms who have received Comirnaty in the recent past. It is noteworthy that, in the present review, we found that most (78.3%) patients experienced symptoms of PTS ipsilateral to the injection site, which suggests that the pathogenesis may involve the local spread of the inoculum.…”
Section: Discussionmentioning
confidence: 99%
“…PTS has also been shown to be associated with immunization, with clinical evidence suggesting that vaccinations against influenza, 71 typhoid, 72 human papillomavirus, 73 and DPT 74 in children are possible etiologic factors. Because cases of PTS have been increasingly reported following COVID-19 vaccination, Kim et al 75 performed a study using disproportionality analysis, and concluded that the risk of neuralgic amyotrophy associated 76 During the COVID-19 pandemic, cases of PTS were reported after both vaccination and infection. In this review, we have summarized the findings associated with 32 cases that developed following vaccination and 36 that developed following infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation of the present work is that we could not analyze the epidemiology of PTS following SARS-CoV-2 vaccination. However, previous research aimed to investigate the link between neuralgic amyotrophy and COVID-19 vaccination using the World Health Organization’s global pharmacovigilance database (VigiBase) [ 84 ]. Of 1,731,147 adverse drug reactions (ADR) reports related to COVID-19 vaccines, the authors identified 335 (0.02%) neuralgic amyotrophy cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, the level of disproportionality observed was not greater than that seen with influenza vaccines. The association between PTS and mRNA-based COVID-19 vaccinations was stronger compared to the ChAdOx1 nCoV-19 vaccine [ 84 ]. Nonetheless, ADRs in countries where reports are not linked to VigiBase might have been omitted.…”
Section: Discussionmentioning
confidence: 99%